(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
The section ‘The Document” offers two chapters of the last report issued by the Antimafia Committee of the City Council of Milan (Comitato di esperti per lo studio e la promozione di attività finalizzate al contrasto dei fenomeni di stampo mafioso e della criminalità organizzata sul territorio milanese, anche in vista della manifestazione Expo Milano 2015), and presented on the 28th October 2016 to the former Mayor of Milan, Giuliano Pisapia, and to the actual Mayor Giuseppe Sala. The excerpts here proposed regard the problems faced by the Committee in the years which have led up to Expo 2015 and the new scenarios of the presence of the Mafia in the area of Milan. Keywords: Committee of experts; Expo 2015; Milan; ‘ndrangheta; public procurements